2021
DOI: 10.1177/0739532921989872
|View full text |Cite
|
Sign up to set email alerts
|

Reporting on transgender victims of homicide: Practices of misgendering, sourcing and transparency

Abstract: Media representations of violence against transgender individuals have implications for public opinion, awareness and policy. A sample (N = 212) of U.S. mainstream news articles about 53 transgender 2018–2019 victims of homicide were studied by content analysis and qualitative methods. About 13% of articles referred to victims by their deadnames (no longer used birthnames), but about 18% of articles drew attention to the harms of misidentification. Deadnaming declined significantly from 2018 to 2019. About 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The current findings also suggest that PTSD symptoms may serve as a significant barrier to continued engagement in HIV prevention programs and may be predictive of early PrEP discontinuation among some TGNB persons. Given the disproportionately high rates of violence enacted against TGNB persons [2,3], it is likely rates of PTSD are elevated as well. Failure to enact laws and policies that recognize and protect TGNB people from discrimination in housing, educational settings, employment, and in health care has enabled the proliferation of ongoing stigma, discrimination, and violence, potentially resulting in higher rates of PTSD [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current findings also suggest that PTSD symptoms may serve as a significant barrier to continued engagement in HIV prevention programs and may be predictive of early PrEP discontinuation among some TGNB persons. Given the disproportionately high rates of violence enacted against TGNB persons [2,3], it is likely rates of PTSD are elevated as well. Failure to enact laws and policies that recognize and protect TGNB people from discrimination in housing, educational settings, employment, and in health care has enabled the proliferation of ongoing stigma, discrimination, and violence, potentially resulting in higher rates of PTSD [2].…”
Section: Discussionmentioning
confidence: 99%
“…Violence against transgender and non-binary (TGNB) persons (persons whose gender identity differs from the sex they were assigned at birth) has deleterious effects on the health and wellbeing of TGNB persons including increasing HIV risk [1][2][3]. While little is currently known about the impact of gender-based violence (GBV) on engagement in HIV prevention behaviors such as pre-exposure prophylaxis (PrEP) among TGNB persons, a recent study found PrEP use 1 3 to be negatively associated with recent experience of violence generally [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The academic literature has found empirical evidence that the media do not always respect the sexual identity of women and men in a situation of transsexuality and they also question its stability (e.g. Åkerlund, 2019; Billard, 2016; Capuzza, 2016; DeJong et al, 2021; Gupta, 2019; Osborn, 2021; Seely, 2021). The wrong body discourse (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Journalists and others are beginning to bring attention to the issue of misgendering (Seely, 2021); the Associated Press Stylebook, for example, is continuously updated to give guidance on how to properly report on the LGBTQ population (Froke, 2018). This is relevant FATAL VIOLENCE AGAINST TRANSGENDER INDIVIDUALS because the media has an influential role in the handling and social response to homicide cases.…”
Section: Law Enforcement Handlingmentioning
confidence: 99%